PROFIL PASIEN BENIGN PROSTATIC HYPERPLASIA DI RSUP DR. M. DJAMIL PADANG TAHUN 2021-2023 - Nurhuda, Mhd; Hamama Pitra, Dian Ayu; Nahzia Septia Fondri; Siana, Yusti; Dian Puspita; Wasbiru, Annita (Yayasan Nusantara Hasana Berdikari, 2025)
Benign Prostatic Hyperplasia (BPH) is a benign enlargement of the prostate gland that often occurs in elderly men due to prostatic stromal and epithelial hyperplasia. The prevalence of BPH increases with age, from 20% in men aged 40 years to 90% at age 80 years, with a global incidence reaching 11.26 million cases in 2019. Clinical symptoms in the form of Lower Urinary Tract Symptoms (LUTS) include irritation such as frequency, urgency, nocturia, and obstruction such as weak stream and hesitancy. Risk factors include age, family history, obesity, diabetes mellitus, and metabolic syndrome. Until now, there has been no data on the profile of BPH patients at Dr. M. Djamil Padang Hospital. Background :This study aims to determine the profile of benign prostatic hyperplasia patients at Dr. M. Djamil Padang General Hospital in 2021-2023. Methode : : This research covers the field of surgery, the type of research used is quantitative descriptive using secondary data. This design was used to view the profile of BPH patients at RSUP DR. M. Djamil Padang 2021 – 2024. Data collection was taken from medical record data. The sampling method was chosen using a simple random sampling technique. The data analysis used is univariate analysis. Result : The results of this study indicate that the highest number of BPH cases were found in the age group of 60-74 years as many as 29 people (54.7%), the highest PSA levels with a value of 0-2.5 ng/dl as many as 46 people (86.8%), the highest prostate volume was found 40-70 ml as many as 26 people (49.1%), the most common therapy performed was surgery as many as 51 people (96.2%), BPH patients who had a history of diabetes mellitus as many as 20 people (37.7%). BPH patients who had a history of hypertension as many as 13 people (24.5%) and there were no patients who had a family history of BPH. Kesimpulan : BPH cases are most often found in men aged 60-74 years. The most common therapy is surgery, especially Tranurethral Resection Prostate (TURP).